Signaling in the Heart - Marín-García, José.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2011)
Signal transduction pathways are at the core of most biological processes and are critical regulators of heart physiology and pathophysiology.  The heart is both a transmitter and dynamic receptor of a variety of intracellular and extracellular stimuli, playing a critical role of an integrator of diverse signaling mechanisms. Alterations in signaling pathways are contributing factors in the development and progression of a broad spectrum of diseases, ranging from dysrhythmias and atherosclerosis to hypertension and the metabolic syndrome.  Targeting specific components of these signaling pathways has been shown to be effective in preclinical studies with significant therapeutic impact. This book brings together current knowledge in cardiovascular cell signal transduction mechanisms, advances in novel therapeutic approaches to improve cardiac function, and discussion of future directions.  Presented from a post-genomic perspective, this exciting book introduces important new ideas in cardiovascular systems biology.  It is an invaluable reference for cardiology researchers and practitioners.
Tools to Study Signaling -- Cell-cycle Signaling, Epigenetic and Nuclear Function -- Signaling in the Endothelium -- Rapid Signaling Pathways -- Growth Factors Signaling Pathways -- Ion Channels Signaling -- Lipids Signaling -- Heart Mitochondria: A Receiver and Integrator of Signals -- Signaling Pathways in Cardiovascular Development -- Signaling in Congenital Heart Disease -- Signaling in the Aging Heart -- Signaling in Endomyocarditis -- Signaling Pathways in Hypertension -- Gene Expression and Signaling Pathways in Myocardial Ischemia -- Signaling in Hypertrophy and Heart Failure -- Signaling in Diabetes and Metabolic Syndrome -- Dysrhythmias/Channelopathies and Signaling Pathways -- Signaling in Atherosclerosis -- Stem Cells Signaling Pathways -- Cardioprotection and Signaling Pathways -- Targeting Specific Pathways -- Future Frontiers in Cardiovascular Signaling.
Keywords: Cardiology; Medical biochemistry; Cardiology; Medical Biochemistry